Information Filtering and Array Algorithms for Descriptor Systems Subject to Parameter Uncertainties - Terra, M.H.; Ishihara, J.Y.; Padoan, A.C. (IEEE transactions on signal processing, 2007)
This paper presents information filters in Riccati recursions and in array algorithms for descriptor systems subject to parameters uncertainties. The filters are developed in filtered and predicted forms. The inversion of the state matrix is avoided in the new information recursive formulas. Therefore, it turns out clear that the invertibility of the state matrix, usually considered in the state-space information recursions, is not necessary. A numerical example is provided to illustrate the performance of the proposed robust array algorithms